Long Non-coding RNA MEG3 Attenuates the Angiotensin II-Induced Injury of Human Umbilical Vein Endothelial Cells by Interacting With p53 - Song, Jingwen; Huang, Songqun; Wang, Kaizhong; Li, Wei; Pao, Lizhi; Chen, Feng; Zhao, Xianxian (Frontiers in Genetics, 2019)
Angiotensin II (Ang II)-induced damage to endothelial cells (ECs) plays a crucial role in the pathogenesis of cardiovascular disease. This study aimed to investigate the role of maternally expressed gene 3 (Meg3) in endothelial cell injury. A lncRNA human gene expression microarray analysis was used to identify differentially expressed lncRNAs in human umbilical vein endothelial cell (HUVECs). Cell viability, apoptosis, and migration were then assessed Ang II-treated HUVECs. qRT-PCR and western blotting were performed to detect the expression level of p53 after Meg3 knockdown and overexpression. We observed that Ang II treatment decreased the Meg3 level in HUVECs. Next, both knockdown of Meg3 and Ang II decreased cell viability, increased apoptotic cell rate and impair migration function in HUVECs. Furthermore, overexpression of Meg3 inhibited cell apoptosis, and increased cell migration by enhancing p53 transcription on its target genes, including CRP, ICAM-1, VEGF, and HIF-1α. Our findings indicate that Meg3 might be associated with cardiovascular disease development.